2004
DOI: 10.1109/tmag.2004.830405
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Pd Nanocluster Seeds by Electrochemical Process for Control of Magnetic Properties in Co/Pd Multilayered Film

Abstract: Pd cluster seeds for a double-layered perpendicular magnetic recording medium composed of a Co/Pd multilayered film and a CoZrNb soft magnetic underlayer (SUL) were fabricated with an electrochemical treatment. By immersing the SUL into an aqueous PdCl 2 solution, the substitution of Pd for Co at the surface of the SUL took place, which was caused by the difference in electrochemical redox potential between Pd and Co. Uniformly distributed Pd clusters with 8 nm in diameter were successfully formed with the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the previous study, the Pd clusters formed by an electrochemical process were reported to show the similar texture to the sputter-deposited Pd (10 nm) seedlayer [6]. However, the crystalline orientations of Co/Pd multilayer deposited on them were quite different.…”
Section: Article In Pressmentioning
confidence: 89%
See 2 more Smart Citations
“…In the previous study, the Pd clusters formed by an electrochemical process were reported to show the similar texture to the sputter-deposited Pd (10 nm) seedlayer [6]. However, the crystalline orientations of Co/Pd multilayer deposited on them were quite different.…”
Section: Article In Pressmentioning
confidence: 89%
“…18 nm. From XPS and XRD analyses, the island-like structures were identified as the metal Pd with face-centered cubic (FCC) structure [6], which is hereafter called ''Pd cluster seeds''. Table 2 shows the values of perpendicular coercivity (H c ) and loop slope parameter, a; of media I and II.…”
Section: Magnetic Properties and R/w Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the electrochemical substitution reaction takes place only at the interface between the surface and the electrolyte solution, a deposited metal is expected to form a very thin film or island-like clusters rather than a thick continuous film, which could be applicable to the seed for the double-layered media. In this section, the Pd formation on a Co-based Co-Zr-Nb SUL as the seed for the sputter-deposited Co/Pd perpendicular magnetization film using the substitution reaction caused by the difference in redox potential between Pd and Co is mainly described [30,31].…”
Section: Control Of Characteristics Of Magnetic Recording Media By Mementioning
confidence: 99%
“…18 nm. From X-ray photospectroscopy and diffractometry, the island-like structure was identified as the Pd metal with fcc structure [30], which is hereafter called "Pd cluster seeds".…”
Section: Control Of Characteristics Of Magnetic Recording Media By Mementioning
confidence: 99%